Kakšen učni načrt si želijo slovenski osnovnošolski učitelji geografije? - Konečnik Kotnik, Eva (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2018)
The objective of this paper is to present part of the research results on Slovenian geography syllabi, which began in an online chat room in the framework of the Meeting of Slovenian Geographers in Maribor in September 2017. Afterwards, it expanded beyond the set framework and continued until April 2018 via the online group "Geolista", in which geography teachers are included. The aim of the research was to determine what kind of syllabi geography teachers in Slovenia want for geography lessons at the primary and secondary levels of education. This paper presents the opinions of the respondents about the basic conceptual orientation of the syllabus for primary school, as well as about its foundation and scope. The respondents evaluated the adequacy of the existing elements of the syllabus and provided suggestions for supplementing/transforming it. The 122 respondents evaluated the existing concept of the geography syllabus for primary school as good, but at the same time, they expressed a wish for a more issue-oriented syllabus. The majority favours a more general and, above all, shorter syllabus for geography lessons in primary school, accompanied by a handbook on how to execute it. A crucial message is that any modernisation of the syllabus should be undertaken in a timely and systematic manner, with sufficient participation of all stakeholders.
Keywords: geografija; osnovne šole; pouk; Slovenija; učni načrti; učni programi za osnovne šole